2015
DOI: 10.1179/1743282014y.0000000132
|View full text |Cite
|
Sign up to set email alerts
|

New national and regional bryophyte records, 42

Abstract: New record of Plagiothecium denticulatum var. obtusifolium from the Parco dell’Aveto (Liguria, Province of Genova)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 101 publications
3
6
0
Order By: Relevance
“…So far, it has been known to be widely distributed in southern South America where it is relatively frequent along the western coast of the continent, ranging from the Argentinean Neuquén and Chilean Cautin Provinces to Tierra de Fuego and extending to the northern maritime Antarctic (Deception Island) and subantarctic South Georgia (Bell, 1974;Ochyra et al, 2008a,b). The species subsequently recurs on the Prince Edward Islands and Îles Crozet (Blockeel et al, 2008), Îles Kerguelen (Cardot, 1916) and Heard Island (Ellis et al, 2015b), as well as on the Île Amsterdam in the warm-south-temperate zone (Ellis et al, 2015a). The present discovery of B. pachydictyon on Tristan da Cunha fills an obvious gap in the range of this species and confirms its phytogeographical status as an amphiatlantic southtemperate species.…”
supporting
confidence: 66%
“…So far, it has been known to be widely distributed in southern South America where it is relatively frequent along the western coast of the continent, ranging from the Argentinean Neuquén and Chilean Cautin Provinces to Tierra de Fuego and extending to the northern maritime Antarctic (Deception Island) and subantarctic South Georgia (Bell, 1974;Ochyra et al, 2008a,b). The species subsequently recurs on the Prince Edward Islands and Îles Crozet (Blockeel et al, 2008), Îles Kerguelen (Cardot, 1916) and Heard Island (Ellis et al, 2015b), as well as on the Île Amsterdam in the warm-south-temperate zone (Ellis et al, 2015a). The present discovery of B. pachydictyon on Tristan da Cunha fills an obvious gap in the range of this species and confirms its phytogeographical status as an amphiatlantic southtemperate species.…”
supporting
confidence: 66%
“…So far, it has been known to be widely distributed in southern South America where it is relatively frequent along the western coast of the continent, ranging from the Argentinean Neuquén and Chilean Cautin Provinces to Tierra de Fuego and extending to the northern maritime Antarctic (Deception Island) and subantarctic South Georgia (Bell, 1974;Ochyra et al, 2008a,b). The species subsequently recurs on the Prince Edward Islands and Îles Crozet (Blockeel et al, 2008), Îles Kerguelen (Cardot, 1916) and Heard Island (Ellis et al, 2015b), as well as on the Île Amsterdam in the warm-south-temperate zone (Ellis et al, 2015a). The present discovery of B. pachydictyon on Tristan da Cunha fills an obvious gap in the range of this species and confirms its phytogeographical status as an amphiatlantic southtemperate species.…”
supporting
confidence: 66%
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 88%